2021
DOI: 10.30714/j-ebr.2021267971
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic extract of Tarantula cubensis (Theranekron®) induce autophagy on gastric cancer cells

Abstract: To evaluate the effects of theranekron in respect of autophagy on gastric cancer that is the fifth leading cancer type worldwide. Metods: In the present study, metastatic AGS and non-metastatic MKN-45 human gastric cell lines were used together with HEK-293 non-cancer cells as controls. Cytotoxic effect of theranekron besides appropriate treatment time was investigated through cell proliferation by using Cell Proliferation assay Kit (MTT) using different concentrations of the drug. The autophagic effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, cell death due to TCAE is not specific to cancer cells, as it was also observed in healthy cells. It has been suggested that cell death may be related to the Ethanol used in the extraction process [38]. It was found in the study that TCAE inhibited tumor development and proliferation and stimulated non-mutagenic tumor suppressor genes [39].…”
Section: Crc + Tcae Crc + Capecitabine Crc + Tcae + Capecitabinementioning
confidence: 99%
“…However, cell death due to TCAE is not specific to cancer cells, as it was also observed in healthy cells. It has been suggested that cell death may be related to the Ethanol used in the extraction process [38]. It was found in the study that TCAE inhibited tumor development and proliferation and stimulated non-mutagenic tumor suppressor genes [39].…”
Section: Crc + Tcae Crc + Capecitabine Crc + Tcae + Capecitabinementioning
confidence: 99%